The Study of Yoruba Literature: an Assessment - Wande, Abimbola (Obafemi Awolowo University Press, 2013)
The history of the study of Yoruba literature dates back to about one hundred and twenty-five years ago. During this period-a lot of collection of oral literature was made and many critical works were published on oral and written literature. It is therefore necessary at this juncture to assess whether the efforts made so far have been in the right direction. The main thrust of this lecture is therefore to assess the study of Yoruba literature from that point of view and to examine whether new directions can be charted for the future progress of this discipline. In doing so we are going to identify certain problems confronting the study of Yoruba literature and propose solutions to these problems.